KEMBALINYA IRIAN BARAT KE NKRI TAHUN 1969 - Rahmad Istiadi Istiadi; Marwoto Saiman Saiman; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack: Historically, the area of ​​Indonesia is the territory of the former Dutch East Indies colony or territory of the former Dutch East Indies. Dutch East Indies archipelago is an area that is separated by seas. Evidence that the Dutch East Indies is fragmentary and does not constitute a single unit is used provided that the territorial sea Indies 3-mile (5.55 km). Indonesia As a nation that never colonized, has a separate area, is clearly a big loss for the people of Indonesia. The circumstances do not support our efforts to realize an independent nation, united, sovereign and towards a just and prosperous nation as stated in the preamble of the 1945 Constitution as a continuation of West Irian issue of dispute between Indonesia and the